SPML: A visual approach for modeling firewall configurations - Trevisani, Kleber Manrique; Garcia, Rogério Eduardo [UNESP] (My University, 2008)
This paper describes a graphical notation for modeling security policy, currently focused on firewalls, named SPML. Using SPML, it is possible to specify graphically the security policy to be implemented by firewalls and to configure firewalls at high level, since the rules can be translated to native configuration. To present the approach proposed, we show how to translate SPML models into firewall configuration.